Evaluation of learning English with the illuminative model in the Fun English program - Risa Ginting (Universitas Pendidikan Indonesia, 2023)
English is an international language used by almost all countries, one of which is Indonesia. English is also very important to learn because it can be used to communicate with many people in various countries. This study aims to determine the level of students' learning skills in English conversation classes, to measure the level of effectiveness of the Fun English program in developing students' English skills, as well as to make improvements and improvements to the Fun English learning program, which is evaluated using the illuminative model. This study used the literature study method, and data collection was carried out using direct observation techniques in the Fun English program. The participants in this study were English course leaders, teachers, and students who participated in an English conversation practice program. The study results show that the learning evaluation implemented in the Fun English program is effective enough to measure students' English proficiency. The Fun English program is quite effective in developing students' English conversation skills, especially in listening, speaking, pronunciation, and fluency.